The feasibility of a national matching service for perfusion education program applicants - Johnson Blaine (The Journal of ExtraCorporeal Technology)
The perfusion profession is experiencing rapid advancement, creating an array of new opportunities for professional growth and educational expansion. However, this increase in demand is juxtaposed with a concerning limitation in the availability of positions for prospective students and may leave many qualified applicants without admission. This letter explores how implementing a national matching service alongside a centralized application service could streamline the application process for perfusion education programs in the United States. Over the last two decades, the number of available positions in perfusion education programs has surged significantly. This growth presents new challenges in recruitment due to varying requirements and timelines, often resulting in unstable matches. A national matching service could standardize acceptances, mitigate unfair practices, and enhance applicants’ and program decision-making. By ensuring a fair and efficient system, the national matching service could support the growing need for qualified healthcare perfusionists and promote the perfusion profession’s advancement.